Depth-structured lineages in the coral Stylophora pistillata of the Northern Red Sea - K. C. C. Capel; I. Ayalon; N. Simon-Blecher; A. Zweifler Zvifler; IC J. Benichou; G. Eyal; D. Avisar; J. Roth; P. Bongaerts; O. Levy (npj Biodiversity)
Abstract Coral reefs are biodiversity hotspots, where new species continue to be discovered. Stylophora pistillata, a depth-generalist coral, is widely distributed throughout the Indo-Pacific and has long been considered the poster child for phenotypic plasticity. It occupies a wide range of reef habitats and exhibits a myriad of gross morphologies. Here, we used reduced representation genome sequencing (nextRAD) to assess the genetic structure of adults and recruits of S. pistillata across shallow and mesophotic populations in the northern Red Sea (Gulf of Aqaba). Across analytical approaches, we observed a complex genetic structure with at least four genetically divergent lineages occurring sympatrically with little to no admixture and structured by depth. Morphological and physiological differences previously documented suggest that the long-considered ecological opportunism of S. pistillata in the Red Sea may, in fact, have a genetic basis. Assessment of both adult colonies and recruits within each of the lineages also revealed the prevalence of local recruitment and genetic structuring across the eight-kilometer section of the Israeli Red Sea coastline. Overall, the observed patterns confirm the presence of undescribed diversity within this model organism for coral physiology and corroborate a broader pattern of extensive undescribed diversity within scleractinian corals.